2023
DOI: 10.3390/cancers15184627
|View full text |Cite
|
Sign up to set email alerts
|

Neo-Adjuvant Treatment in Primary Resectable Pancreatic Cancer: A Systematic Review and PRISMA-Compliant Updated Metanalysis of Oncological Outcomes

Raffaello Roesel,
Letizia Deantonio,
Lorenzo Bernardi
et al.

Abstract: Background: Despite advances in treatment, the prognosis of resectable pancreatic adenocarcinoma remains poor. Neoadjuvant therapy (NAT) has gained great interest in hopes of improving survival. However, the results of available studies based on different treatment approaches, such as chemotherapy and chemoradiotherapy, showed contrasting results. The aim of this systematic review and meta-analysis is to clarify the benefit of NAT compared to upfront surgery (US) in primarily resectable pancreatic adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Our results were in line with those of a previous meta-analysis in some respects [ 8 ] but different from those of the Prep-02/JSAP05 study, which showed a survival benefit of NAC-GS [ 25 ]. A recent meta-analysis also suggested that NAT is associated with a lower risk of development of lymph node metastasis, an improved R0 resection rate, and improved recurrence-free and overall survivals in patients with resectable disease [ 11 ]. Our negative results may be ascribed to the small number of patients, the different NAC regimens used, and the short duration of NAT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results were in line with those of a previous meta-analysis in some respects [ 8 ] but different from those of the Prep-02/JSAP05 study, which showed a survival benefit of NAC-GS [ 25 ]. A recent meta-analysis also suggested that NAT is associated with a lower risk of development of lymph node metastasis, an improved R0 resection rate, and improved recurrence-free and overall survivals in patients with resectable disease [ 11 ]. Our negative results may be ascribed to the small number of patients, the different NAC regimens used, and the short duration of NAT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the application of NAC has been expanded to resectable PDAC [ 11 , 23 ]. The Prep-02/JSAP05 study showed that NAC using gemcitabine plus S-1 provided significant survival benefit, while the PREOPANC study showed that NACRT using gemcitabine-based NAC and radiotherapy was associated with an improved median survival period [ 24 , 25 ].…”
Section: Evidence Of the Benefits Of Adjuvant/neoadjuvant Chemotherap...mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis of randomized studies showed statistically significantly improved negative resection margin rates and overall survival of patients with pancreatectomies for borderline resectable PDAC with neoadjuvant therapies compared with up-front surgery [94]. For resectable PDAC, another meta-analysis showed significantly higher rates of negative resection margins and negative lymph nodes after neoadjuvant therapies than upfront surgery [95]. As mentioned earlier, negative lymph nodes appear to be an important determinant of survival after PD with concurrent colectomies [39].…”
Section: Oncological Outcomes Of Pd With Concurrent Colectomiesmentioning
confidence: 91%